Taxonomy of the genus Paris L. (Melanthiaceae) in Vietnam - Nga, Nguyen Quynh; Huyen, Pham Thanh; Truong, Phan Van; Toan, Hoang Van (Academia Journal of Biology, 2016)
Paris L. is a small genus distributed widely in Eurasia. In Vietnam Paris occur in evergreen broad-leaved forests in some mountainous areas of the North and the Central highlands. Due to over-exploitation as well as habitat loss, populations of some Paris species are seriously declining. This genus has not been studied extensively in Vietnam. The aim of this study was to define the morphological characteristics of the genus Paris in Vietnam. Morphological description, dichotomous key for identification, ecology and distributions of the genus in Vietnam are reported. The results show that this genus in Vietnam comprises 8 species and 2 varieties, possesing unilocular ovary with parietal placenta.